Integrasi Teknologi dan Tradisi : Kajian Model TPACK (Technological, Pedagogical, and Content Knowledge) dalam Pembelajaran Maharah Qirā’ah Berbasis Teks Arab Era Turki Utsmani - Maulida, Farkha (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
Arabic language learning, particularly in the aspect of mahārah qirā’ah (reading skill), still faces various challenges, such as students’ low reading interest in classical Arabic texts and difficulties in understanding linguistic structures, vocabulary, and the historical–cultural contexts underlying the texts. On the other hand, the development of digital technology in the era of 21st-century learning demands pedagogical innovations that are able to bridge the Islamic scholarly tradition with the needs and characteristics of modern learners. One approach considered relevant in addressing these challenges is TPACK (Technological, Pedagogical, and Content Knowledge), which emphasizes the integration of technology, pedagogy, and content in the learning process. This research analyzes how the TPACK (Technological, Pedagogical, and Content Knowledge) approach to enhance maharah qirā’ah (reading proficiency) through learning based on Arabic texts from the Ottoman period. This research seeks to explore how the integration of technology, pedagogy, and content can enhance students’ ability to read classical texts while fostering their interest in and understanding of the language, culture, and Islamic intellectual traditions. The method used is a library research approach and this study draws its primary data from Ottoman Arabic texts, supported by secondary materials such as books, scholarly articles, and theses. The results suggest that the employment of TPACK allows teachers to present classical texts in interactive digital formats, utilizing multimedia, collaborative platforms, and PowerPoint media to facilitate student comprehension. This strategy can improves reading skills, nurtures critical thinking, cultural appreciation, and students’ spiritual character. Therefore, integrating classical texts and technology through TPACK can serve as a relevant Arabic language learning model, connecting Islamic scholarly traditions that. correspond to 21st-century learning expectations